THE INFLUENCE OF WORK CULTURE AND EMPLOYEE ENGAGEMENT ON WORK PRODUCTIVITY IN BARANTIN - Suwarno Tri Widodo; Suryono Efendi; Lijan Poltak Sinambela (Bajang Institute, 2025)
This study aims to analyse the influence of work culture and employee engagement on the productivity of employees at the Indonesian Quarantine Agency (Barantin). The background of this study is based on the challenges faced by public organisations, which often encounter low employee engagement and fluctuations in productivity due to a bureaucratic work culture and a lack of adaptability to change. This study employs a quantitative method using purposive sampling techniques on 160 employees, with data analysis conducted using Structural Equation Modelling (SEM) via SmartPLS. The results indicate that work culture has a positive and significant impact on work productivity, with a coefficient of 0.494, a t-statistic of 6.778, and a p-value of 0.000. A strong work culture, encompassing integrity, collaboration, innovation, and responsibility, has been proven to enhance employee performance. Additionally, employee engagement also has a positive and significant impact on productivity, with a coefficient of 0.460, a t-statistic of 6.334, and a p-value of 0.000. Employee engagement, measured through the indicators of vigor, dedication, and absorption, drives increased motivation, focus, and work quality. The R-square value of 0.861 indicates that the work culture and employee engagement variables can explain 86.1% of the variation in work productivity, while the predictive relevance (Q²) of 0.725 indicates that the model has high predictive powerThis finding emphasises the importance of strengthening a positive work culture and increasing employee engagement to achieve optimal and sustainable productivity in public organisations.